Phosphate fertilization strategies and placement effects on grain crop yields in subtropical no-till Oxisols - Andria Paula Lima; Sandra Mara Vieira Fontoura; Renato Paulo de Moraes; Cimélio Bayer; Luke Gatiboni; Tales Tiecher (Revista Brasileira de Ciência do Solo)
ABSTRACT Subtropical Oxisols have a high phosphate adsorption capacity and consequently lower phosphorus (P) availability. Therefore, correct management of phosphate fertilization in grain crop rotations is essential to increase the P-use efficiency and minimize potential environmental impacts. This study aimed to evaluate, in soils with medium and high initial P level, fertilization strategies (crop and system fertilization) and placement’s effects (banded P and broadcast) on soil available P, crop yield, and P use efficiency. Two field trials were installed on an Oxisol (Humic Hapludox – Latossolos) cultivated with a crop rotation with corn or soybean in the summer, and cereals in the winter. Crop yield, P use efficiency, and soil available P in the 0.00-0.10 and 0.10-0.20 m layers were evaluated during eight growing seasons. Three years of phosphate fertilization increased the P content of the 0.00-0.20 m layer above the critical level (8 mg dm-³) in the soil with medium initial P and maintained the P status above the critical level in the soil with high initial P. The P-rich environment in the 0.00-0.10 m soil layer was sufficient to support high-yield grain crops with low response to fertilization strategies and placement. However, four years of banded P fertilization on high initial P soil resulted in a greater increase in P content in the 0.10-0.20 m layer compared to broadcast P. In the field trial with medium initial available P content, there was a greater response to phosphate fertilization, leading to a significant increase in grain yields when compared to the control treatment with no P, especially for barley (50 % increase). Over four years of evaluation, banded P, regardless of the fertilization strategy (crop or system), proved effective in increasing crop yield (for one crop of black oat and three crops of corn) and P use efficiency (one crop of corn). System fertilization in a high P export environment should be adopted only in soils with available P content above the critical level and after at least four years of using diverse winter cover crops (grass + legume). Otherwise, P fertilization at every sowing (crop fertilization) remains more appropriate for intense grain production systems.